Frey Syndrome in Infancy - Carlota Lopes; Laura Martins; Paulo Varela (Publicaciones Permanyer, 2023)
Frey syndrome is rare in children and often erroneously attributed to food allergy. It is caused by damage to the auriculotemporal nerve, hence the alternative name of the auriculotemporal syndrome. This study describes a case of Frey syndrome in a 2-year-old girl with flushing without sweating on the left cheek after eating tomato and citrus fruit with a medical history of traumatic forceps-assisted delivery. Recognition of this condition is vital to avoid unnecessary medical costs and procedures and provide reassurance to parents and primary care providers in this benign condition with a self-limited course.